1997
DOI: 10.1144/gsl.sp.1997.120.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Rock weathering in blockfields: some preliminary data from mountain plateaus in North Norway

Abstract: The formation of blockfields is a process usually attributed to weathering. In mountain areas this is generally assumed to be mechanical weathering (frost shattering). Evidence from two high plateaus [900 and 1350 m above sea level (a.s.1.)] in North Norway (c. 70 ~ N) suggests that chemical action is at least as important as mechanical activity in blockfield formation. The bedrock in both areas consists of complex banded gabbros. Blockfields circumscribe ice masses and are generally > 1 m thick. They contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The field observations of the basal part of the stone runs and the associated analyses provide new insights into the origin of the stone run, that partly contradict previous interpretations. Therefore, the objectives of this paper are three-fold: (i) to review the scientific literature from 1839 to 2007 dealing with the description of the Falklands stone runs and the various hypotheses accounting for the origin; (ii) to bring to the debate new observations and analyses that lead to the proposal of an alternative model of stone run formation and evolution; and (iii) to discuss the validity of this model based on comparisons with previous interpretations of the Falklands stone runs and of blockfields from other areas such as Tasmania (Caine, 1968a(Caine, ,b, 1972(Caine, , 1983, North Norway (Rea et al, 1996;Whalley et al 1997Whalley et al , 2004, and North Québec-Labrador (Marquette et al, 2004;Gray et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The field observations of the basal part of the stone runs and the associated analyses provide new insights into the origin of the stone run, that partly contradict previous interpretations. Therefore, the objectives of this paper are three-fold: (i) to review the scientific literature from 1839 to 2007 dealing with the description of the Falklands stone runs and the various hypotheses accounting for the origin; (ii) to bring to the debate new observations and analyses that lead to the proposal of an alternative model of stone run formation and evolution; and (iii) to discuss the validity of this model based on comparisons with previous interpretations of the Falklands stone runs and of blockfields from other areas such as Tasmania (Caine, 1968a(Caine, ,b, 1972(Caine, , 1983, North Norway (Rea et al, 1996;Whalley et al 1997Whalley et al , 2004, and North Québec-Labrador (Marquette et al, 2004;Gray et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This has been emphasized by geomorphological and geological investigations over the last 20-30 years in low-latitude environments not directly affected by Quaternary glacial activity, especially in Australia and South Africa (Young 1983;Fried & Smith 1992;Gale 1992). This in turn, has been supported by an increasing number of studies in western Europe where evidence has accumulated to support the survival of pre-glacial landforms (Mitchell 1980), extensive deeply weathered Tertiary material (Fitzpatrick 1963;Hall & Sugden 1987) and preQuaternary weathering and associated land surfaces (Lidmar-Bergstr6m & Ase 1988;Lidmar-Bergstr6m 1995;Whalley et al 1997).…”
Section: The Case For Integration and Collaborationmentioning
confidence: 87%
“…This term is used within this thesis as a collective description for the entire range of clast supported periglacial boulder deposits. While block deposits are generally considered to be indicators of past periglacial conditions, there has been significant literature (Van Steijn et al 2002, Andrè 2003, Andrè et al 2008) that have suggested that they are of polygenetic origin and may have developed at least in part under deep chemical weathering during Tertiary and interstadial warm periods of the Quaternary (Rea et al 1997, Andrè et al 2008. The widespread evidence for clay weathering products and rounded nature of boulders associated with some block deposits, do suggest that block deposits in part owe their formation to chemical weathering (Caine 1983, Rea et al 1997.…”
Section: Block Depositsmentioning
confidence: 99%
“…While block deposits are generally considered to be indicators of past periglacial conditions, there has been significant literature (Van Steijn et al 2002, Andrè 2003, Andrè et al 2008) that have suggested that they are of polygenetic origin and may have developed at least in part under deep chemical weathering during Tertiary and interstadial warm periods of the Quaternary (Rea et al 1997, Andrè et al 2008. The widespread evidence for clay weathering products and rounded nature of boulders associated with some block deposits, do suggest that block deposits in part owe their formation to chemical weathering (Caine 1983, Rea et al 1997. The principle driver of formation of block deposits has been debated particularly in the Falkland Islands (Andrè et al 2008, Hansom et al 2008, Wilson et al 2008, however studies of the deposits in the Falklands and similar studies from Scandinavia which present evidence for chemical weathering still acknowledge the role Late Quaternary periglacial conditions have played on block deposit development (Rea et al 1997, Whalley 1997, Van Steijn et al 2002, Andrè et al 2008, Goodfellow et al 2009).…”
Section: Block Depositsmentioning
confidence: 99%
See 1 more Smart Citation